2018
DOI: 10.14635/ipsic.2018.115.7
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre Agresividad e Inflexibilidad Psicológica Durante la Adolescencia: Resultados Preliminares

Abstract: El objetivo de esta investigación es determinar si la inflexibilidad psicológica actúa como variable predictora de la agresividad en una muestra de adolescentes, considerando la perspectiva de género. Se trata de una investigación novedosa dado que no existe literatura sobre la relación entre ambas variables, y la inflexibilidad psicológica apenas ha sido estudiada en población adolescente. Para ello se diseñó un estudio descriptivo transversal en el que han participado 499 estudiantes de educación Secundaria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There is evidence that PsyInflex is a transdiagnostic process present in a myriad of externalizing and internalizing problems (Monestès et al, 2018), and relates with physical aggression and dating violence among college students (Shorey et al, 2014), but research with adolescent samples is very limited. With Spanish adolescents, preliminary data confirmed the relation of PsyInflex with overt and relational TDV (Villanueva et al, 2018), and recent studies showed that PsyInflex with prejudice thoughts predicts personal distress (Valdivia-Salas, Martin-Albo, et al, 2021), which, in turn, relates to both physical and relational TDV (Valdivia-Salas, Jiménez, et al, 2021).…”
Section: Psychological Flexibility and Psychological Inflexibilitymentioning
confidence: 60%
“…There is evidence that PsyInflex is a transdiagnostic process present in a myriad of externalizing and internalizing problems (Monestès et al, 2018), and relates with physical aggression and dating violence among college students (Shorey et al, 2014), but research with adolescent samples is very limited. With Spanish adolescents, preliminary data confirmed the relation of PsyInflex with overt and relational TDV (Villanueva et al, 2018), and recent studies showed that PsyInflex with prejudice thoughts predicts personal distress (Valdivia-Salas, Martin-Albo, et al, 2021), which, in turn, relates to both physical and relational TDV (Valdivia-Salas, Jiménez, et al, 2021).…”
Section: Psychological Flexibility and Psychological Inflexibilitymentioning
confidence: 60%